Hydrocarbon potential assessment of the lacustrine fan delta reservoirs in the Lower Cretaceous syn-rift Xing’anling Formation in the Beier Sag, Hailar Basin, Northeast China - Cui, Xin; Li, Jianghai; Jiang, Hongfu; Yan, Hongxing; Qi, Qingpeng (Frontiers in Earth Science, 2023)
Efficient exploration and development of oil and gas resources in complex geological environments continue to pose significant challenges for the energy industry. The localization and extraction of reservoirs in basins with complex structures, developed faults, and scattered sedimentary sand bodies are topics of international interest. One such basin, the Hailar Basin in northeastern China, represents a complex geological environment with heterogeneous distributions of oil and gas reserves, along with variable reservoir conditions, leading to challenges in hydrocarbon exploration and extraction. The Sudeert oil field, situated within this basin, is known for its high productivity; nevertheless, the underlying factors responsible for its success are not yet fully comprehended. Based on seismic, logging, and core data from the Sudeert oil field, as well as previous research, this study comprehensively analyzed the sedimentary environment, sedimentary facies characteristics, sand body distribution patterns, vertical stacking relationships of sand bodies, and hydrocarbon accumulation potential of the oil reservoirs in the Lower Cretaceous Xing’anling Formation in the Sudeert oil field. The Xing’anling Formation I and II oil reservoirs are deposited in a fan-delta front sedimentary environment, and the sedimentary microfacies that are conducive to the development of reservoir sand bodies include underwater distributary channels, underwater natural levees, estuary dams, front silt beds, and turbidite sands. Among them, the underwater distributary channel microfacies is the main depositional facies for the development of reservoir sand bodies. Three major depositional patterns of fan lobes can be identified within this depositional system: 1) isolated, 2) contact, and 3) superimposed lobes. Different combinations of lobes developed in different blocks and resulted in different sand body depositional patterns. The isolated lobes mainly developed in the western oil-producing (B28 block) due to the scarcity of sand and slowly increasing accommodation space. The contact lobes mainly developed in the central oil-producing block (B14 block) due to sufficient sediment supply and steadily increasing accommodation space across a wide area. The superimposed lobes mainly developed in the southeast oil-producing block (B16 block) due to sufficient sediment input and steadily increasing accommodation space within a restricted area. In the whole study area, the superimposed lobe pattern is the most favorable depositional pattern and forms the highest-quality reservoirs because of the high degree of sand body connectivity. These results also highlight the utility of sedimentary patterns and sand body assemblage studies for the oil exploration and development of similar rifted basins.